Nomenclatural notes on Phlegmariurus dentatus (Lycopodiaceae) - Arana, Marcelo D. (Phytotaxa, 2016)
The Lycopodiaceae comprise 16 monophyletic genera grouped into three subfamilies (Arana & Øllgaard 2012, Øllgaard 2012, 2014). One of the recently resurrected genera is Phlegmariurus Holub (1964: 21) with ca. 400 species formerly treated under Huperzia Bernhardi (1801: 126) in the Neotropics and Palaeotropics, leaving Huperzia s.s. with 15–25 species restricted to the Holarctic and austral Andean regions (Arana & Øllgaard 2012).